2019
DOI: 10.1111/tbj.13655
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in transgender female‐to‐male individuals: A case report of androgen receptor‐positive breast cancer

Abstract: Highlight the challenges associated with managing breast cancer in female‐to‐male (FtM) transgender individuals. This is a rare entity, requiring nuanced decision‐making regarding surgery as well as adjuvant therapies given the unique hormonal environment seen in individuals taking exogenous androgen as part of their gender identity. Contemporary case report derived from our clinical experience. Discussion focuses on a brief summation of all known cases of female‐to‐male breast cancer in FtM individuals descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 25 publications
0
37
0
1
Order By: Relevance
“…(2019) [ 19 , 25 ] Case report and retrospective cohort study 29 Yes, incidental finding Positive 4 High-grade DCIS Negative ER+ Fundytus et al. (2019) [ 26 ] Case report 48 Yes, incidental finding Positive 19 Invasive ductal carcinoma Unknown ER+, PR+, AR+, HER2- Gooren et al. (2013) [ 17 ] Retrospective cohort study 27 Yes, incidental finding Unknown 3 Tubular adenocarcinoma Unknown ER +, PR+ Gooren et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) [ 19 , 25 ] Case report and retrospective cohort study 29 Yes, incidental finding Positive 4 High-grade DCIS Negative ER+ Fundytus et al. (2019) [ 26 ] Case report 48 Yes, incidental finding Positive 19 Invasive ductal carcinoma Unknown ER+, PR+, AR+, HER2- Gooren et al. (2013) [ 17 ] Retrospective cohort study 27 Yes, incidental finding Unknown 3 Tubular adenocarcinoma Unknown ER +, PR+ Gooren et al.…”
Section: Resultsmentioning
confidence: 99%
“…The JBI and CARE checklist recommend presenting the patient’s historical and current information as a visual timeline, but none of the studies did accordingly [8] . Eight case reports did not clearly describe the treatment outcomes of the breast cancer; no post-intervention clinical condition was reported [ 22 , 24 , 32 ], no harmful events as a result of interventions were described [ 22 , 24 , 25 , 30 , 32 , 33 ], or the patient had not completed treatment yet [ 26 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…6 Incidental finding of breast carcinoma in the mastectomy specimen was observed in 1 patient in Gooren et al's series and in 1 patient reported by Fundytus et al in 2019. 6,7 In Fundytus et al's report, the patient underwent a previous breast reduction as GAS. Additional mastectomy for aesthetic purpose 15 years later revealed a BCa on histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Additional mastectomy for aesthetic purpose 15 years later revealed a BCa on histopathology. 7 In 2011, Shao et al published 2 cases of trans men under testosterone therapy who did not go through GAS but who developed carcinoma for which mastectomies were required. 8 In comparison with previously reported cases, our patient was the youngest patient with BCa after mastectomy, and his CSH treatment was short (2.5 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation